Floodable Park Landscape Model as Adaptive Infrastructure: Integrating Blue-Green Technology and Community Education for Urban Flood Mitigation in Bandar Lampung, Indonesia - Ina Winiastuti Hutriani; Muhammad Saddam Ali; Zulvita Amanda; Susan Krisanti; Bagas Arianto; Cindy Romauly Elysabeth Manurung; Muhammad Arya Wibowo; Luthfie Adli Wistoro (Research in Education, Technology, and Multiculture, 2026)
Bandar Lampung City faces escalating flooding challenges driven by rapid urbanization and climate change, necessitating the adoption of nature-based solutions. This study proposes a floodable park landscape model that integrates blue-green infrastructure with community education programs, serving as an alternative to traditional structural mitigation. The research focused on Barunaria Field in the Panjang District, a site identified as a high-priority flood-prone area through previous GIS-based spatial analysis. The study utilized a modified LaGro landscape design framework across three stages: inventory and site selection, analysis and synthesis, and conceptual development. Primary data were gathered via field surveys, temporal environmental measurements of temperature, humidity, and noise, behavioral observations, and semi-structured interviews with residents, supplemented by documentation reviews. Analysis revealed several critical factors contributing to flooding, including low infiltration capacity from extensive impermeable surfaces, high runoff coefficients, and acidic soil conditions. Additionally, the site suffered from waste accumulation, noise pollution, and a lack of social or educational infrastructure. The resulting modular design integrates rain gardens, bioswales, permeable pavements, and infiltration wells with social and agricultural zones, including urban farming areas, amphitheaters, and pedestrian pathways. A distinguishing feature of this model is the incorporation of Lampung’s Tapis batik motifs into functional landscape elements. It also establishes educational zones for disaster risk reduction and urban farming, functioning as a practical site for environmental education. The proposed model facilitates recreation and food production during dry periods while functioning as a retention system during the rainy season to reduce runoff. This culturally grounded, modular approach provides a framework for sustainable flood mitigation that supports environmental education and community resilience through ecological and social benefits. Keywords: Blue-green infrastructure; Community education; Floodable park; Local wisdom; Urban agriculture.